Hyaluronic filler for lip augmentation and scar correction in cleft lip Egyptian patients (Journal of Pharmaceutical Negative Results, 2022)
Objectives: The goal of the current study was to assess how hyaluronic acid dermal filler was applied and how well it worked to conceal lip abnormalities after surgery in a group of Egyptian cleft lip and palate (CLP) patients.Methods: This research included sixteen female patients with unilateral lip scars between 15 and 20 years of age. Hyaluronic acid dermal filler (HADF) was injected with needle in upper lip at the scar site. Evaluation was done clinically and by digital photography before and after the procedure. Visual Analog Scale (VAS) from (0-10) was used as a patient satisfaction assessment survey. Follow up period was made one week and one month post injection.Results: All these patients noted a significant improvement in their lip scars following HA filler injection with better psychological state. The VAS satisfaction rate assessment was high and ranging from 7-9 with a mean of (8.0 ± 0.9). Clinical observation showed no long-term complications, however patients complained of some discomfort due to fibrosed tight lips during the injection.Conclusion: HADF is a safe noninvasive temporary method used for masking cleft lip scars and restoring vermilion border volume which promotes the appearance and psychological status of the CL patient.